The Influence of Brand Equity and Customer Bonding on the Loyalty of Beauty MSME Consumers with Satisfaction as a Mediating Variable - Efendi, Efendi; Anggreani, Jenni; Butarbutar, Novita; Panggabean, Esther Praja Anggriany; Sudirman, Acai (IJBLE Scientific Publications Community Inc., 2023)
In the beauty industry, business competition is very tight so consumer satisfaction is very important to maintain a business in a competitive market. The main aim of this research is to analyze the influence of brand equity and customer bonding on the loyalty of beauty MSME consumers with satisfaction as a mediating variable. The results of this research confirm that brand equity has a significant effect on consumer satisfaction. Customer bonding does not have a significant influence on consumer satisfaction. The results further confirm that brand equity, customer bonding, and consumer satisfaction have a significant effect on consumer loyalty. The mediating effect of satisfaction can mediate the relationship between brand equity and consumer loyalty, while the relationship between customer bonding and consumer loyalty. consumer satisfaction is not able to mediate it. It is hoped that the implications of this research can provide a fundamental contribution in the form of supporting information regarding strategic steps and strengthening models in optimizing the resources owned by creative industry business players, especially for beauty MSMEs